The effect of the grass setaria megaphylla on the growth of pinus patula. - Christie, Stuart, Ian (My University, 1995)
A three-year study was undertaken In the province of Mpumalanga, South Africa to Investigate the competitive effects of the grass Setaria megaphylla on the growth of the tree species Pinus patula. A replacement series field trial, where six different competition regimes were Implemented, clearly demonstrated the suppressive effects of S. ( Abbreviation abstract )
Submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy Faculty of Science University of Witwatersrand Johannesburg SOUTH AFRICA
Keywords: Pinus patula -- South Africa.; Setaria -- South Africa.; Trees -- Growth; Forest ecology -- South Africa; Competition (biology) -- South Africa